N6-Methyladenosine RNA Demethylase FTO Promotes Gastric Cancer Metastasis by Down-Regulating the m6A Methylation of ITGB1 - Wang, Duo; Qu, Xiujuan; Lu, Wenqing; Wang, Yizhe; Jin, Yue; Hou, Kezuo; Yang, Bowen; Li, Ce; Qi, Jianfei; Xiao, Jiawen; Che, Xiaofang; Liu, Yunpeng (Frontiers in Oncology, 2021)
Abnormal RNA m6A methylation is known to lead to the occurrence and progression of multiple cancers including gastric cancer (GC). However, the integrative effects of all m6A methylation regulators on GC prognosis is unclear. Our research aimed to globally analyze the prognosis value of all 33 m6A RNA methylation regulators in GC by univariate and multivariate Cox regression analysis. Among all 33 m6A RNA methylation regulators, Fat mass and obesity-associated protein (FTO), an m6A demethylase, was identified as a key prognostic risk factor on overall survival (OS) of GC patients. Then, we found that FTO could promote GC cell migration and invasion abilities, and predicted that ITGB1 was a demethylated target of FTO. Knockdown (KD) of FTO significantly down-regulated ITGB1 expression at both mRNA and protein levels and augmented ITGB1 mRNA m6A modification level. Moreover, overexpression of ITGB1 could partially reversed FTO-KD-inhibited migration and invasion of GC cells. Our study discovered that FTO was an independent risk factor for overall survival (OS) of GC patients and FTO could promote GC metastasis by upregulating the expression of Integrin β1(ITGB1) via decreasing its m6A level. These results revealed FTO as a potent GC biomarker for prognosis prediction as well as a potential target in GC treatment.